Speculative Design in a Graduate Program in Informatics: Students Perception and Practical Application: A Novel Approach for Supporting Information Systems Education - Loutfi, Marcelo Soares; Siqueira, Sean Wolfgand Matsui (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Information and Communication Technologies (ICTs) frequently prioritize technical efficiency and process optimization, often overlloking the nuanced and enduring cultural, social impacts and other subtle and long-term effects of technology. Problem: In the education of IT professionals, there is an excessive emphasis on technical disciplines at the expense of sociotechnical aspects, which are fundamental for understanding and applying technology in a conscious, ethical, and responsible manner. Solution: This research advocates for the incorporation of Speculative Design to prompt students to perceive technology beyond its technical dimension. Additionally, it aims to enhance the understanding of student perceptions and feedback.IS Theory: The sociotechnical theory is used to support the interaction between social and technological systems in the context of Speculative Design in IT education. Method: The Action Research method is applied in the educational environment, creating a learning experience where graduate students in Informatics develop and implement their own Speculative Design approaches. Through a questionnaire, we extract their perceptions. Results: Despite initial challenges, students acknowledged the benefits of Speculative Design, such as the development of critical thinking and creativity, positively impacting their analytical and creative skills. Contribution: The study contributes to Information Systems education by introducing Speculative Design as a novel approach, surpassing the strictly technicist perspective.